2007
DOI: 10.1103/physrevd.75.087304
|View full text |Cite
|
Sign up to set email alerts
|

Path to metallicity: Synthesis of CNO elements in standard BBN

Abstract: We perform a reanalysis of the production of CNO elements in a standard Big Bang Nucleosynthesis scenario. The CNO yields in BBN are suppressed by the low density of the plasma, Coulomb barrier effects and the short time scales involved. Yet, the inclusion of nuclides and reactions traditionally disregarded may lead to an increase relevant enough to affect the pristine Population III stars. After a critical reanalysis and upgrade of the nuclear network our results show no major discrepancies with the ones obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
148
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(156 citation statements)
references
References 21 publications
8
148
0
Order By: Relevance
“…These results are consistent with those of Iocco et al [33] but slightly lower than those of Vonlanthen et al [62]. Detailed CNO, B and Be isotopic abundances, compared with those from Iocco et al [33] can be found in Table 7, together with H, He and Li isotopic abundances compared with our previous work. As expected, the extension of the network does not alleviate the 7 Li discrepancy between calculations and observations.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…These results are consistent with those of Iocco et al [33] but slightly lower than those of Vonlanthen et al [62]. Detailed CNO, B and Be isotopic abundances, compared with those from Iocco et al [33] can be found in Table 7, together with H, He and Li isotopic abundances compared with our previous work. As expected, the extension of the network does not alleviate the 7 Li discrepancy between calculations and observations.…”
Section: Resultssupporting
confidence: 82%
“…The minimum value of the initial CNO abundance that would affect Pop III stellar evolution is estimated to be as low as 10 −13 (in number of atoms relative to hydrogen, CNO/H) for the less massive ones [32]. This is only two orders of magnitude above the Standard Big Bang Nucleosynthesis CNO yield, using the current nuclear reaction rate evaluations of Iocco et al [33]. In addition, it has been shown that Pop III stars evolution is sensitive to the triple-alpha ( 12 C producing) reaction and can be used to constrain the possible variation of the fundamental constants [34].…”
Section: Bbn Production Of Heavier Elementsmentioning
confidence: 96%
See 2 more Smart Citations
“…Provided that the properties of dark matter allow the formation of dark stars, objects of this type are expected to be among the first stars forming in the history of the universe and therefore to have extremely low metallicities Z, possibly at the level given by Big Bang nucleosynthesis (this implies Z ∼ 10 −9 mainly due to Li; e.g., Iocco et al 2007). All models therefore assume primordial abundances of H and He.…”
Section: Model Atmosphere Spectramentioning
confidence: 99%